2001
DOI: 10.1093/oxfordjournals.jbchem.a002874
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Human Matrix Metalloproteinase 7 (Matrilysin) with the Inhibitors Thiorphan and R-94138

Abstract: The effects of the metalloproteinase inhibitors thiorphan and R-94138 on the matrilysin-catalyzed hydrolysis of (7-methoxycoumarin-4-yl)acetyl-L-Pro-L-Leu-Gly-L-Leu-[N(3)-(2,4-dinitrophenyl)-L-2,3-diamino-propionyl]-L-Ala-L-Arg-NH(2) [MOCAc-PLGL(Dpa)AR] were examined. The inhibitor constants (K(i)) of thiorphan and R-94138 for matrilysin at pH 7.5, 25 degrees C were determined to be 11.2 and 7.65 microM, respectively. From the temperature dependence of the K(i) values at pH 7.5, the standard enthalpy change (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…However, thiorphan has recently been shown to bind other metalloproteases including matrix metalloproteinase 7 (matrilysin). 32 Matrilysin expression is up-regulated in corneal basal epithelial cells after wounding and has been speculated to be involved in epithelial migration and proliferation. 33 Therefore, an interaction between matrilysin and thiorphan may have contributed to our observed improvement in wound closure kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…However, thiorphan has recently been shown to bind other metalloproteases including matrix metalloproteinase 7 (matrilysin). 32 Matrilysin expression is up-regulated in corneal basal epithelial cells after wounding and has been speculated to be involved in epithelial migration and proliferation. 33 Therefore, an interaction between matrilysin and thiorphan may have contributed to our observed improvement in wound closure kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported the high stability and denaturation properties of matrilysin [12,13]. The interaction of matrilysin with synthetic inhibitors has been studied, and the significance of hydrophobic interactions has been suggested in the recognition of the inhibitors at the active site of matrilysin [14]. Green tea catechins, especially those with a galloyl group, inhibit matrilysin in non-competitive manner with a K i of 0.47-1.65 µM [15].…”
Section: Introductionmentioning
confidence: 99%
“…The pH-dependence of matrilysin activity exhibits an extraordinarily broad bell-shaped curve, indicating the involvement of at least two ionizable groups in its catalytic mechanism [14,16]. (the numbering of the amino acid residues of pro-matrilysin is applied in this paper to activated matrilysin, beginning at number 78 for the N-terminal tyrosine residue [17]) or a water molecule bound to the active zinc (Lewis acid) is considered to be the ionizable group of the acidic side with pK e1 [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) The development of MMP-7 inhibitors is thought to be of potential therapeutic benefit. We have reported that alcohols, 12) synthetic MMP inhibitors thiorphan and R-94138, 13) and lignans 14) inhibit MMP-7 activity in a competitive manner, while green tea catechins 15,16) and a fluorescent probe, 8-alininonaphthalene 1-sulfonate (ANS), 17) inhibit it in a non-competitive manner. MMP-7 exhibits a broad bell-shaped pH profile of MMP-7 activity with acidic and alkaline pK a (pK e1 and pK e2 ) values of about 4 and 10.…”
mentioning
confidence: 99%